The World of South African Music: A Reader. Lucia, Christine, editor. 2005. Cambridge Scholars press: Newcastle, UK. Includes List of musical Examples (xii- xiv), a List of Illustrations (xv-xvi), References, a List of Sources and an Index, 368 pp. - Watkins, Lee (International Library of African Music, 2007)
pages: 112-113
Keywords: South Africa; African Music